Health consequences for E-waste workers and bystanders—a comparative cross-sectional study - Fischer, Damian; Seidu, Fatima; Yang, Jennie; Felten, Michael K.; Garus, Cyryl; Kraus, Thomas; Fobil, Julius N.; Kaifie, Andrea (International Journal of Environmental Research and Public Health, 2020)
Informal e‐waste recycling is associated with several health hazards. Thus far, the main focus of research in the e‐waste sector has been to assess the exposure site, such as the burden of heavy metals or organic pollutants. The aim of this study was to comprehensively assess the health consequences associated with informal e‐waste recycling. A questionnaire‐based assessment regarding occupational information, medical history, and current symptoms and complaints was carried out with a group of n = 84 e‐waste workers and compared to a control cohort of n = 94 bystanders at the e‐waste recycling site Agbogbloshie. E‐waste workers suffered significantly more from work‐related injuries, back pain, and red itchy eyes in comparison to the control group. In addition, regular drug use was more common in e‐waste workers (25% vs. 6.4%). Both groups showed a noticeable high use of pain killers (all workers 79%). The higher frequency of symptoms in the e‐waste group can be explained by the specific recycling tasks, such as burning or dismantling. However, the report also indicates that adverse health effects apply frequently to the control group. Occupational safety trainings and the provision of personal protection equipment are needed for all workers.
CRIS-Team Scopus Importer:2023-09-25
Keywords: Agbogbloshie; Back pain; Drug abuse; Ergonomic burden; Occupational exposure; Occupational health and safety